A Novel Application of the Hemostatic Net in Aesthetic Breast Surgery: A Preliminary Report. (16th March 2022) - Goddard, Naveen Virin; Pacifico, Marc D; Campiglio, Gianluca; Waterhouse, Norman
Abstract: Background: Obtaining optimum breast aesthetics can be challenging in secondary aesthetic breast surgery, particularly with poor-quality skin, when downsizing implants, and in cases where patients will not accept additional mastopexy scars. Most techniques described in these cases rely on internal suturing and capsulorrhaphy, which can lack precision in tailoring the skin over the internal pocket. Objectives: The aim of this study was to present the authors' experience with utilizing the hemostatic net to help address a range of challenging breast cases in their practices. Methods: A multicentre retrospective analysis of patients undergoing aesthetic and reconstructive breast surgery between 2019 and 2021 was conducted. A database was established to record patient demographics, indications for surgery, surgical technique, and complications. Following capsulorrhaphy, the hemostatic net was applied in as many rows as required with monofilament sutures and removed 3 to 7 days postoperatively. Results: Twenty-four women (aged 23-67 years) underwent aesthetic or reconstructive breast surgery with the hemostatic net. This approach optimized stabilization of the inframammary fold and redraping of lax skin or irregularities in the skin envelope. At follow-up review, only 1 instance of the net failing to successfully redrape the skin was seen. Conclusions: The application of the hemostatic net is an option for patients who might otherwise require mastopexy but refuse to accept the scars. The technique has now been extended to primary cases where implant malposition or skin tailoring issues are anticipated, thus securing its place as a part of the surgical armamentarium. Level of Evidence: 4: